Eras Tour Outfit: Pemaknaan Tubuh Pemuda Melalui Outfit pada Konser Taylor Swift - Ramiyati, Asmi (Universitas Gadjah Mada, 2024)
Appropriate outfit choices are an important aspect of presenting a professional appearance at a music concert. Each concert is closely associated with the identity of the singer, reflected in the concert concept, choreography, stage setting, and costumes. This research will examine the significance of outfits and friendship bracelets worn by young Taylor Swift fans, who have become a defining feature of her The Eras Tour. This research employs a combination of digital ethnography methods, specifically utilizing Instagram and TikTok platforms, and participant observation techniques. The results of this study indicate that the use of outfits by Taylor Swift fans tailored to specific albums reflects the fans' strong connection with Taylor's songs, as evidenced by certain outfit modifications. This form of connection can be observed among young people who engage in the voluntary practice of sewing, modifying, and searching for outfits that align with their preferred Taylor Swift album. Furthermore, this form of connection is disseminated and reinforced by fans at The Eras Tour concerts through the exchange of friendship bracelets. Each fan creates bracelets inspired by Taylor Swift's albums, titles, or lyrics, which they then exchange with other fans at the venue.